RESULTS OF THE RESEARCH OF MORPHOFUNCTIONAL PARAMETERS OF DRY SKIN IN WOMEN IN DIFFERENT AGE GROUPS - D. S. Panchenko; O. Y. Kirgizova (Acta Biomedica Scientifica, 2017)
In cosmetology, there is a wide range of methods and means to correct aesthetic deficiencies and symptoms of involutional changes, in particular, dry skin. It is not sufficient to assess the patient visually while deciding which tactics of dry skin complex correction and prevention to choose. Skin dryness has a cyclical character with a tendency to age deterioration, so it is very important to have rational beauty care, adapted to the physiology and skin structure. Operating principles of instruments to assess hydration, hydrolipidic skin mantle, elasticity, flexibility and transepidermal water loss are reviewed. The authors discuss the key goals and practical value of the described biophysical study methods as well as possible impact of age, environment and conducted treatment on the dynamics of the indices. The article presents an overview of the main methods for studying the morphofunctional condition of the skin: determination of skin moisture, elasticity, greasiness, trans-epidermal water loss, as well as skin ultrasound examination. We discuss the main objectives and practical significance of the described methods of non-invasive skin studying, as well as possible influence of age on the dynamics of dry skin of women of different age groups. This paper deals with the clinical aspects of non-invasive methods for diagnostics of various abnormalities and pathological changes in the skin. The necessity of their application in cosmetology is substantiated.